combine the like terms.
add 6 to both sides.
divide by 11 on both sides.
11p - 6 = -39
11p - 6 + 6 = -39 + 6
11p = -33
p = ?
MATH - 0.4P+1=0.7P-2 IS IT 3
math - help me solve this 4p+5-7p=-1
math - simplify this expression 4p + 9 + (-7p)+ 2=
math - Which of the following is not a polynomial ? [A] x0 [B] x+y2 +3z -1+5a [C...
algebra - Provide A Reason For Each Step Of Simplifying The Expression 3 3(4p-1...
alg - Divide: p^2 + 4p - 5 / p^2 + 7p + 10 * p + 4 / p - 1 a) p + 2 b) p + 2 / p...
equations & inequalities - 1.simplify this expression 4p+9+(-7p)+2=? a.3p+11 b....
chemistry - list the sequnce in which the following orbitals fill up: 1s , 2s , ...
math - what property is being used in the equation 4p+7+7+4p.
math - I know i'm a slow bunny and the answer is in my face but please help! (4p...